Coronavirus disease 2019 in patients with sickle cell disease: A cross-sectional study from Jazan Province, Saudi Arabia - Abdulaziz Alhazmi; Wesam Ali Moafa; Jalal Madkhali; Othman Saifain; Faizah Alyahyawi; Ons Adhabi; Ahmad Ali Alharbi (Wolters Kluwer Medknow Publications, 2022)
Objectives: To assess the prevalence of coronavirus disease 2019 (COVID-19) infection among sickle cell disease (SCD) patients in Jazan region and to determine the impact of COVID-19 on the SCD population. Methods: This was an observational, descriptive, cross-sectional study using a self-administrated questionnaire directed to SCD patients in Jazan to assess the prevalence of COVID-19. The data were analyzed using a t-test and Chi-square test. Results: A total of 188 responses were received and only 96 SCD patients were included (mean age is 24 years). About half of the study samples (53%) of the study population were male. About 11% of patients with SCD were diagnosed with COVID-19. Vaso-occlusive crisis was reported in 73% and a single patient presented with acute chest syndrome. About three-fourths of patients (73%) were admitted to the hospital and most of them experienced mild symptoms and one patient was treated in the intensive care unit. Conclusion: SCD patients are at risk of SARS-CoV-2 infection. In the absence of comorbidities, patients with SCD are not at increased risk of COVID-19 mortality, but a higher admission rate is reported. SCD patients with COVID-19 may have a milder clinical course, compared to other populations with comorbidities such as diabetes and hypertension, and this may be due to proinflammatory adaptation of the immune system. Larger studies including epidemiological and molecular details are needed to enhance our understanding of how SARS-CoV-2 could affect patients with SCD.